Valoração da paisagem da unidade de conservação Parque Estadual do Parque Estadual do Poeta e Repentista Juvenal de Oliveira - Campina Grande/PB: uma proposta de ordenamento territorial - Souza, Alexsandro Silva (2017)
This research refers to a study done in a Conservation Unity (CU) of integral protection, trying to offer planning orientations based on the study of the landscape evaluation through a systemic bias. The Poeta Repentista Juvenal de Oliveira's CU Park State in the city of Campina Grande - PB has no management and needs scientific knowledge to legitimate its implementation requirement, for it is an unregulated CU which has to deal with other territoriality impositions. Thus, the main goal of this work is to value and evaluate the CU landscape, through the application of the global herbal landscape valuation methodology LANBIOEVA (acronym for Landscape Biogeographic Evaluation), trying to identify natural and cultural values so that one can have elements that could give the right planning strategies. Have been valued, as well, landscapes placed nearby the CU, as a way to understand the background in which the studied area can be inserted, enabling one to propose indications of compatible and suitable uses for the aims of a Park type CU. Although it is a phytogeographic transition zone, it has been observed in the floristic surveys a meaningful amount of Caatinga species, some of them endemic, rare or even endangered. It has been noted that the Poeta Repentista Juvenal de Oliveira's CU Park State has landscape typologies with interesting values from a natural and cultural point of view, but unsettling values from a threatening point of view, obtaining, thus, a score that appears superior to the boreal and temperate climate landscapes. The east landscapes showed floristic, natural and cultural values similar to those found inside the CU, but with a low threat degree, being potential for the conservation and annexation to the CU bounds. The conflicting uses in the CU and the consequent threatenings to the natural resources of the studied area are imminent and unobservant to the environmental legislation, therefore there must be urgent interventions so that the degradation setting can be reversed. The CU and nearby areas landscapes show themselves with great potentials as providers of ecosystem services, what justifies the necessity of the regualarization of a protected area and a territorial planning that allow nature's conservation and preservation.